PERAN KOPERASI DALAM PEMBERDAYAAN SUMBER DAYA MANUSIA DALAM MASYARAKAT - Nurfaisah Nurfaisah; Samsuri Samsuri; Waldi Waldi (Universitas Ichsan Sidenreng Rappang, 2025)
Cooperatives play a strategic role in strengthening the people’s economy while enhancing human resource (HR) quality through a participatory economic approach. This study aims to analyze the role of cooperatives in empowering human resources within society by reviewing relevant previous research. The study employed a descriptive qualitative method with a literature review technique, drawing on seven primary national and international journal sources published between 2021 and 2025. The findings reveal that cooperatives function not only as economic institutions but also as spaces for social learning, solidarity building, and individual capacity development. Through the principle of economic democracy, cooperatives contribute to improving skills, financial literacy, and the values of justice and mutual cooperation. Furthermore, women’s participation in cooperatives has been shown to enhance economic independence and social involvement at the community level. However, challenges remain in governance, digital literacy, and technological adaptation. Therefore, strengthening managerial capacity, encouraging digital innovation, and ensuring supportive government policies are essential to reinforce the cooperative’s role in sustainable human development.